Physical Characteristics Meat of Various Pig Breed (Jurnal Ilmu dan Teknologi Hasil Ternak, 2007)
This study was conducted to investigate physical characteristics of various pig breed.  The materials used in this study were nine pigs (three Yorkshire, three Landrace, and three Duroc), and they were about 7 – 8 months old, weighing 90 – 100 kg. The meat examined, was  Longissimus dorsi muscle.  They were heated of 50oC, 75oC, 100oC. This study applied a Completely Randomized Design with a 2-factor nesting pattern using cooking repeatition for three times. The factors were pig breed and the cooking temperature degrees. The treatment indicating differences were examined by using Duncan Multiple Range Test (DMRT). The differences of pig breeds did not provide differences on quality for pH, WHC, cooking loss and Aw. Within quality differences (P<0.01), there would  be tenderness, elasticity, shear force, and meat water content. Cooking gave quality differences (P<0.01) on pH, tenderness, elasticity, shear force, WHC, cooking loss, Aw and water content. Cooking loss and water content decreased with the increase of cooking treatment temperature. Meat pH on the temperature of 50 oC decreased in comparison with raw meat and it would increase with the enhancement in cooking treatment. Tenderness, elasticity, shear force, and WHC of the meat decreased at 75 oC and they could get enhancement as the temperature achieving 100 oC. Duroc tended to have more tenderness, elasticity, and higher shear force rates in comparison with Yorkshire and Landrace. Keywords: Pig breed,  Cooking, Physical quality